2003
DOI: 10.1002/cphc.200300689
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Spin Clusters: New Synthetic Approaches and Neutron Scattering Studies

Abstract: We review our recent work in the field of molecular spin clusters and single-molecule magnets, showing how inelastic neutron scattering (INS) can be used to determine magnetic exchange interactions and anisotropy splittings. A general introduction to neutron scattering precedes selected examples, building upon the first determination of exchange coupling in a transition metal complex using INS, through anisotropic exchange in cobalt(II) spin clusters to the determination of exchange interactions in a dodecanuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 69 publications
2
60
0
Order By: Relevance
“…Perhaps most significantly, groups now routinely report field-dependent magnetisation alongside variable temperature susceptibility, and there is also now significant use of inelastic neutron scattering (INS), largely driven by Güdel in the first instance. 11 The number of parameters used in the spin Hamiltonian has also increased, primarily due to the realization that the anisotropy of the single ions is frequently of significance in determining physical behaviour. Recent work has also suggested that the form of the exchange interactions used is also vital, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps most significantly, groups now routinely report field-dependent magnetisation alongside variable temperature susceptibility, and there is also now significant use of inelastic neutron scattering (INS), largely driven by Güdel in the first instance. 11 The number of parameters used in the spin Hamiltonian has also increased, primarily due to the realization that the anisotropy of the single ions is frequently of significance in determining physical behaviour. Recent work has also suggested that the form of the exchange interactions used is also vital, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the SMMs which have been synthesized so far are based on 3d metal ions, and several of them were studied by INS, but mostly for the transitions within the ground-state multiplet (for reviews see Basler et al, 2003;Bircher et al, 2006). However, being related to anisotropy and not the exchange splittings, these studies shall not be further discussed here; Fe 8 may serve as a representative example.…”
Section: A Introductionmentioning
confidence: 99%
“…These can be used to calculate the INS intensity for a transition i!f, which is proportional to the scattering function S ab A C H T U N G T R E N N U N G (Q,w) given in Equation (2), [35] in which j,j' is the number of the Cr III centre; a and b stand for Cartesian coordinates x, y, z; Ŝ j,a is the a component of the spin operator Ŝ j at position r j ; j ii is the initial state of a transition with energy E i ; j fi the final state with energy E f ; p i is the Boltzmann population factor of state j ii and Q is the scattering vector or the momentum transfer between neutron and sample, respectively.…”
mentioning
confidence: 99%